Investigating the Influence of Characteristics of the New Product Introduction Process on Firm Value: The Case of the Pharmaceutical Industry. (September 2018) - Sharma, Amalesh; Saboo, Alok R.; Kumar, V.
Scholars identify several benefits of new product introductions (NPI), yet prior literature largely overlooks how the process of NPI generates marketplace insights and influences subsequent products. Building on the concept of absorptive capacity, the authors argue that the influence of products on firm value depends on process characteristics, namely, the pace, irregularity, and scope of NPI. Using data collected from multiple sources for products introduced by pharmaceutical firms between 1991 and 2015 and robust econometric methods that account for endogeneity and unobserved heterogeneity, this study reveals that pace and scope have an inverted U-shaped effect on firm value, whereas irregularity negatively influences firm value. Moreover, strategic emphasis and product complexity negatively moderate the relationship of the irregularity and scope of NPI with firm value. This research documents the importance of adopting a portfolio approach to the sequential introduction of new products and incorporating insights gained from previous product introductions; it cautions managers against evaluating products in isolation. The authors discuss the economic significance of these results and provide actionable guidance for managers.